Global Insights into Sustainable Public Service Innovation: A Bibliometric Exploration of Research - Sulmiah, Sulmiah; Sakawati, Herlina; Widyawati, Widyawati (Program Pascasarjana Universitas Negeri Makassar, 2024)
Public service innovation has become a critical element in achieving sustainable development, driven by the increasing complexity of societal challenges and the need for responsive and equitable solutions. This study explores global trends in sustainable public service innovation through bibliometric analysis, using data from Scopus between 2019 and 2024. The results show a growing recognition of the importance of sustainability in public services, particularly influenced by global sustainability targets and technological advancements. The findings also highlight significant trends in digital transformation, stakeholder collaboration, and of organizational capacity in driving sustainable public services. Furthermore, the study reveals geographical disparities in publication output, with higher contributions from Europe and Latin America. This study highlights the importance of further exploration in underrepresented regions, particularly in the Global South. Future research should bridge this gap and encourage interdisciplinary collaboration to strengthen sustainable public service innovation. The integration of technology, stakeholder engagement, and strategic organizational frameworks are essential to advance sustainable governance practices.